Health effects of different dietary iron intakes: a systematic literature review for the 5th Nordic Nutrition Recommendations - Magnus Domellöf; Inga Thorsdottir; Ketil Thorstensen (Food & Nutrition Research, 2013)
Background : The present literature review is part of the NNR5 project with the aim of reviewing and updating the scientific basis of the 4th edition of the Nordic Nutrition Recommendations (NNR) issued in 2004. Objective : The objective of this systematic literature review was to assess the health effects of different intakes of iron, at different life stages (infants, children, adolescents, adults, elderly, and during pregnancy and lactation), in order to estimate the requirement for adequate growth, development, and maintenance of health. Methods : The initial literature search resulted in 1,076 abstracts. Out of those, 276 papers were identified as potentially relevant. Of those, 49 were considered relevant and were quality assessed (A, B, or C). An additional search on iron and diabetes yielded six articles that were quality assessed. Thus, a total of 55 articles were evaluated. The grade of evidence was classified as convincing (grade 1), probable (grade 2), suggestive (grade 3), and inconclusive (grade 4). Results : There is suggestive evidence that prevention or treatment of iron deficiency (ID) and iron deficiency anemia (IDA) improves cognitive, motoric, and behavioral development in young children, and that treatment of IDA improves attention and concentration in school children and adult women. There is insufficient evidence to show negative health effects of iron intakes in doses suggested by the NNR 4. There is insufficient evidence to suggest that normal birth weight, healthy, exclusively breast-fed infants need additional dietary iron before 6 months of life in the Nordic countries.An iron concentration of 4–8 mg/L in infant formulas seems to be safe and effective for normal birth weight infants. There is probable evidence that iron supplements (1–2 mg/kg/day) given up to 6 months of age to infants with low birth weight (<2,500 g) prevents IDA and possibly reduce the risk of behavioral problems later on. There is probable evidence that ID and IDA in pregnant women can be effectively prevented by iron supplementation at a dose of 40 mg/day from week 18–20 of gestation. There is probable evidence that a high intake of heme iron, but not total dietary, non-heme or supplemental iron, is associated with increased risk of type 2 diabetes (T2D) and gestational diabetes. Conclusions : Overall, the evidence does not support a change of the iron intakes recommended in the NNR 4. However, one could consider adding recommendations for infants below 6 months of age, low birth weight infants and pregnant women.